Effects of kefir fermented milk beverage on sodium dextran sulfate (DSS)-induced colitis in rats. Issue 1 (January 2023) - Nascimento da Silva, Karina; Fávero, Aline Garnevi; Ribeiro, William; Ferreira, Caroline Marcantonio; Sartorelli, Patrícia; Cardili, Leonardo; Bogsan, Cristina Stewart; Bertaglia Pereira, Joice Naiara; de Cássia Sinigaglia, Rita; Cristina de Moraes Malinverni, Andréa; Ribeiro Paiotti, Ana Paula; Miszputen, Sender Jankiel; et al.
Abstract: Background and aim: The etiopathogenesis of inflammatory bowel disease (IBD) is associated with different factors such as genetic, infectious, immunological, and environmental, including modification of the gut microbiota. IBD′s conventional pharmacological therapeutic approaches have become a challenge due to side effects, complications from prolonged use, and higher costs. Kefir fermented milk beverage is a functional food that has demonstrated multiple beneficial effects including anti-inflammatory and antioxidant activity. Alternative therapeutic strategies have been used for IBD as more natural products with low-cost and easy acquisition. The aim of this study is to evaluate the anti-inflammatory effects of kefir fermented milk beverage on sodium dextran sulfate (DSS)-induced colitis in rats. Methods: We used 4 groups to perform this study: baseline control (BC), kefir control (KC), 5% untreated DSS-induced colitis (DSS), and 5% DSS-induced colitis treated with kefir (DSSK). The animals received fermented kefir milk beverage ad libitum for six days and the disease activity index was recorded daily. Colon samples were processed for Transmission Electron Microscopy and histopathological evaluation. We analyzed short fatty chain acids through the fecal sample using gas chromatography. Results: Kefir supplementation was able to reduce the clinical activity index and inflammatory process evidenced by decreased neutrophil accumulation, decreased reticulum edema, and increased autophagosomes. Also, showed a trend to increase the levels of acetate and propionate. Conclusions: Our results suggest that kefir fermented milk beverage may have an anti-inflammatory effect minimizing the intestinal damage of DSS-induced colitis. Graphical abstract: Image 1 Abstract : Inflammatory bowel disease, Ulcerative colitis, Probiotics, Kefir, short-chain fatty acids.